PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING TERHADAP DIMENSI BERNALAR KRITIS SISWA SEKOLAH DASAR - Tamara, Dede; Salimi, Asmayani; Ghasya, Dyoty Aulia Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research was conducted because the achievement of critical reasoning dimensions in fourth grade students of SDN 7 Sungai Raya has not been achieved as a whole. An alternative to overcome this problem is to apply a student-centered learning model, for example the Problem-Based Learning model. The purpose of this research is to test the effect of the Problem-Based Learning learning model on the achievement of students' critical reasoning dimensions. The method used in this research is a pre-experimental design type of one group pre-test and post-test design. The sample in this study was 20 students of class IVF SDN 7 Sungai Raya. The instruments used in this study were observation sheets and test sheets. The data analysis used in this study used statistical analysis techniques, namely inferential analysis assisted by the SPSS 25 application. Based on the analysis of the research data, the results showed that there was an effect of the use of the Problem-Based Learning learning model on the achievement of students' critical reasoning dimensions, as evidenced by the results of the Wilcoxon test which showed a sig value of 0.000